Topics in cryptography B - developing a blockchain-based for voting system - Tan, Wen Jun (Nanyang Technological University, 2023)
Nowadays, we can achieve everything online. This including online shopping, chatting with friends around the world, pay your house loan and much, much more. This includes voting! E-voting is a way that allows people to cast their vote electronically. As compared to traditional voting, E-voting eliminates the need to print out the ballot paper, queuing at allocated polling station to cast their vote. E-voting also can increase voter turnout rate. Because with the ease of this technology to allow voters to cast their votes online, rather than going down to the physical polling station. Despite of these benefits, E-voting has its disadvantages. Firstly, the security of E-voting system. The system must be legitimate, safe, accurate. Secondly, the transparency of system and its processing method of the data may not be very transparent to publics. Since the process is entirely electronic, this could lead to vote manipulations by people, since publics hardly to verify the counts. To overcome these issues, Blockchain technology came into the picture, where it can convert the traditional voting process into electronical based and provides security protection, transparency to the voting system. The main goal of this project is to present how Cryptography works in a web-based voting system, together with adopting Blockchain concepts.